Interleukin 1 beta (IL-1 beta) processing in murine macrophages requires a structurally conserved homologue of human IL-1 beta converting enzyme. - Molineaux, S M (1993)
Murine interleukin 1 beta (IL-1 beta) convertase (mICE) was identified in cytosolic extracts of peritoneal exudate cells (PECs) and macrophage cell lines. mICE cleaves both the human and mouse IL-1 beta precursors (pIL-1 beta) at sites 1 and 2 but fails to cleave a human pIL-1 beta (Asp116 to Ala) mutant at site 2, indicating that Asp is required to the left of the scissile bond. Ac-Tyr-Val-Ala-Asp-amino-4-methyl coumarin, patterned after site 2 of human pIL-1 beta, is a fluorogenic substrate for mICE, while the tetrapeptide aldehyde Ac-Tyr-Val-Ala-Asp-CHO is a potent inhibitor (Ki = 3 nM) that prevents generation and release of mature IL-1 beta by PECs (IC50 = 7 microM). Cloning of a full-length 1.4-kb cDNA shows that mICE is encoded as a 402-aa proenzyme (p45) that can be divided into a prodomain (Met1-Asp122), followed by a p20 subunit (Gly123-Asp296), a connecting peptide (Ser297-Asp314), and a p10 subunit (Gly315-His402). At the amino acid level, p45, p20, and p10 are 62%, 60%, and 81% identical with human IL-1 beta convertase (hICE). The active site Cys284 lies within a completely conserved stretch of 18 residues; however, Ser289 in hICE, which aligns with the catalytic region of serine and viral cysteinyl proteases, is absent from mICE. Expression in Escherichia coli of a truncated cDNA encoding Asn119-His402 generated active enzyme, which was autocatalytically processed at three internal Asp-Xaa bonds to generate a p20 subunit (Asn119-Asp296) complexed with either p11 (Ala309-His402) or p10. Recombinant mICE cleaves murine pIL-1 beta accurately at the Asp117-Val118 bond. The striking similarities of the human and murine enzymes will make it possible to assess the therapeutic potential of hICE inhibitors in murine models of disease.